CSR, NILAI PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN PADA INDUSTRI PERTAMBANGAN DAN MANUFAKTUR DI INDONESIA - Farah Margaretha; Chandra Gunadi Witedjo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This study was done in order to determine the reversible effect from company CSR action on ROA and ROE, as well as to measure the company value using Tobin’s Q, size and leverage also used as control variable. In order to test the impact of the variables described above, 28 samples of mining and manufacturing company listed in BEI during two periods are used, which is for three years long, 2009-2010. Analysis model of the data used is the classical assumption, multiple regression and t test. Based on t test result CSR has no effect on Tobin’s Q. CSR is also found to have no relation to ROA and ROE, except for environmental dimension for which negative effect was found to ROE. The last finding of this study was ROA has a positive effect on environmental and labor disclosure of CSR, and no effect was found on the community dimension. ROE subsequently found to have a positive effect on the labor and community disclosure, while no effect was found on environmental dimension of CSR. As for that result it is recommended for companies to put CSR as an investment that should be considered in the process of capital budgeting, as CSR is a huge investment and still not being considered by investors and public.